Experiential Effects of Dialectical Inquiry, Devil's Advocacy and Consensus Approaches to Strategic Decision Making - Schweiger, David M.; Sandberg, William; Rechner, Paula L. (Academy of Management Journal, 1989)
This longitudinal laboratory study of fast-advancing middle managers involved in strategic planning compared the effectiveness of dialectical inquiry, devil's advocacy, and consensus approaches to group strategic decision making. Compared to consensus groups, groups using dialectical inquiry and devil's advocacy made significantly higher quality decisions. Members of such groups reported more reevaluation of their own assumptions and recommendations but lower acceptance of their group's decisions than members of consensus groups. There were no differences between dialectical inquiry and devil's advocacy groups. Experience in using the three decision-making approaches improved decision quality, critical reevaluation levels, and the reactions of group members and reduced the time required to reach decisions.